Identidade física do juiz no direito processual civil brasileiro: análise dos motivos da omissão do Código de Processo Civil de 2015 - Pedro Mallet Kneipp (2023)
The research, materialized in this dissertation, aims to understand the reasons for the omission of the judge's physical identity in CPC/2015 from the historical analysis of the legislative process. Once identified, the reasons were tested in order to demonstrate whether they are supported by currently valid assumptions. To achieve the result, two prevous steps were necessary. First, the historical evolution of the judge's physical identity in the Brazilian civil procedure, since CPC/1939, was analyzed. It was possible to visualize three phases of the judge's physical identity in this context: rigid phase, flexibility phase and omission phase.Then, even in the context of legislative omission, the judge's physical identity was related to the other elements of orality, to the cooperative process model and, also, to the humanization of the process. Finally, after analyzing the legislative process of CPC/2015, the reasons for the omission were identified, then they were tested, including statistical analysis of data collected from the brazilian judiciary, concluding that it's not possible to affirm that the reasons are supported by currently valid premises.